Survival Adaptations to the Covid-19 of Muslims in Thailand's Deep South - Hanakamae, Roshidah; Saleah, Abdullateh; Sidae, Weayosof; Daemohleng, Salma; Anohkasae, Ismael; Alfariti, Ahmad; Sa-i, Ismaie (MENARA : Journal of Islamic and Contemporary Issues, 2025)
This research aims to 1) study the impact of the COVID-19 situation on the adaptation of Thai Muslims in terms of occupation and health; 2) study the attitudes of Thai Muslims towards compliance with the orders and measures to prevent the spread of the coronavirus disease 2019 (COVID-19) of the Sheikhul Islam Office; and 3) study the adaptation patterns of Thai Muslims to the COVID-19 situation using Islamic cultural practices. The sample group used in the attitude survey was 400 people. The sample group used for the interviews was the mosque committee in the three southern border provinces, 10 people per province, totaling 30 people; Muslim scholars in the three southern border provinces, 10 people per province, totaling 30 people; the general public who are Muslims in the three southern border provinces, totaling 10 people per province, totaling 30 people, totaling 90 people. The group discussion forum consisted of 10 general public people, 5 religious leaders, 5 village health volunteers, 5 Muslim scholars, 1 representative from the Sheikhul Islam Office, and the Islamic Committee of Yala Province. The analysis of quantitative and qualitative data obtained from questionnaires, interviews, and conversations will use the content analysis and summary methods, as well as the compilation and analysis of documents and various evidence collected by separating and synthesizing the data obtained according to the intended objectives, checking the comprehensiveness of the data, and presenting it in a descriptive report to support the discussion of the results. The research results found that 1) The impact of the COVID-19 situation on the adaptation of Thai Muslims in terms of occupation has resulted in reduced income and some are unemployed, laid off, and in debt. The health of those who contracted COVID without being vaccinated and those who contracted COVID after being vaccinated is different. That is, those who contracted COVID after being vaccinated have less severe symptoms than those who contracted COVID without being vaccinated. 2) Thai Muslims in the three southern border provinces have a positive attitude towards the measures to prevent the spread of the coronavirus disease 2019 (COVID-19) of the Sheikhul Islam Office because such measures are consistent with Islamic principles, namely preserving human life or protecting the security of life because this principle aims to protect life from physical harm or harm to any part of the body and will cover the treatment and prevention of health. Or eliminate various diseases 3) Adaptation of Thai Muslims to the COVID-19 situation by using Islamic cultural ways in practicing religion during the COVID-19 situation. Thai Muslims can adapt by applying knowledge about practicing religion during the COVID-19 situation correctly through the announcement of the Sheikhul Islam Office. The format for adapting to religious practice will consist of refraining from doing things that are mandatory, approving things that are forbidden, and changing the format of religious practice.